Study of clinical profile, pathological and functional changes in contralateral ear in patients of chronic suppurative otitis media - Nigam, Ritu; Bairwa, Rajesh Kumar; Goel, Ayesha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Since unilateral chronic suppurative otitis media (CSOM) does not look to be an isolated entity, but rather a series of constitutional events that affect both ears. The aim of the present study is to study the clinical profile, pathological and functional changes in contralateral ear in patients of CSOM. Methods: Three thundred CSOM patients were studied in the Department of Otorhinolaryngology and Head and Neck Surgery. Patients were examined with otoscope after complete history and sociodemographic taking. Results: CSOM was more prevalent among females (54%) of young age group (41.6%) and with lower socioeconomic status (46%). Right ear was mostly affected (52.66%). Majority had discharge with hearing impairment (49.3%), 32.3% had ear discharge and 13.6% had hearing impairment and majority had pars tensa perforation (82.66%). In mucosal type CSOM, in CLE majority had abnormal tympanic membrane TM, of them majority had thinning (17.33%) and out of 65 patients with pars tensa retraction, majority had Grade I (22.17%). In squamosal type of CSOM, in CLE, 75% had abnormal TM, out of that 34.61% had pars tensa retraction and of that 23.07% had Grade I. Conclusions: Abnormal contralateral ear was more prevalent. Mucous type of CSOM has a chance forming various grades of tympanic membrane retraction, tympano sclerosis, thin healed membrane in the contralateral ear whereas squamous type of CSOM has a greater chance of contralateral ear involvement like, retraction granulation.